2023
DOI: 10.1002/pls2.10081
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion for pharma applications: An update

Abstract: This paper aims to give an overview of our current research and development on hot-melt extrusion (HME) for pharmaceutical formulation and drug delivery.Unfortunately, a large percentage of marketed drugs (40%) and those in the development pipeline (90%) are poorly water soluble. We use a few examples to show that solubility of APIs can be drastically improved by using HME to mix them with different biocompatible polymers and playing with the various process parameters (extrusion temperature, screw speed, scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The encapsulation process was performed by direct addition of the star copolymer/drug acetone mixture into PBS (10 mL) under vigorous stirring. The solution was then left at room temperature to allow the acetone to evaporate over 24 h. In an industrial scale, because of cost, safety, and environment protection, an alternative is to use twin‐screw extruder, which allows to conduct drug loading without any solvent 51,52 . The detail of the industrial twin‐screw extrusion process can be found in a review by Li et al 53 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The encapsulation process was performed by direct addition of the star copolymer/drug acetone mixture into PBS (10 mL) under vigorous stirring. The solution was then left at room temperature to allow the acetone to evaporate over 24 h. In an industrial scale, because of cost, safety, and environment protection, an alternative is to use twin‐screw extruder, which allows to conduct drug loading without any solvent 51,52 . The detail of the industrial twin‐screw extrusion process can be found in a review by Li et al 53 …”
Section: Methodsmentioning
confidence: 99%
“…The solution was then left at room temperature to allow the acetone to evaporate over 24 h. In an industrial scale, because of cost, safety, and environment protection, an alternative is to use twin-screw extruder, which allows to conduct drug loading without any solvent. 51,52 The detail of the industrial twin-screw extrusion process can be found in a review by Li et al 53 The loading studies were conducted following the ultrafiltration centrifugal method according to literature. [54][55][56] In this method, the free drug is separated from the drug entrapped inside the carriers during ultrafiltration.…”
Section: Drug Loading Proceduresmentioning
confidence: 99%
“…The use of HME to produce filaments with defined shapes and properties is crucial for the success of 3D printing in pharmaceutical applications [51]. The continuous and cost-efficient nature of HME makes it an attractive manufacturing process for drug-delivery systems [52]. Moreover, the use of HME in combination with 3D printing technology also supports the development of personalized medicine and targeted drug-delivery systems [53].…”
Section: Key Elements Of Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
“…ASDs may be defined as a solid dispersion that involves the melting of a solid mixture of API and a suitable vehicle, usually polymers that form eutectic mixtures [51,65]. The polymer or "solvent", interferes with the ordered arrangement of the crystalline API and thereby transforms the mixture into an amorphous solution [51,52,65,66]. The use of FDM in conjunction with ASDs of APIs with low solubility has shown that 3D-printed tablets derived as such show considerable improvement in the solubility of the API [67].…”
Section: Fdm 3d Printing and Amorphous Solid Dispersions (Asds)mentioning
confidence: 99%